Pengaruh Keterlibatan Pelanggan dan E-commerce terhadap Kinerja UMKM di Jepara dengan Inovasi Produk sebagai Variabel Intervening - Ilma Nafia; Nurul Komaryatin (SENTRI: Jurnal Riset Ilmiah, 2026)
MSMEs face challenges in improving business performance amid increasingly fierce competition and shifts in consumer behavior in the digital era. Low customer engagement and suboptimal e-commerce use remain key constraints on leveraging digital opportunities. This study aims to analyze the effects of customer engagement and e-commerce utilization on MSME performance, with product innovation as a mediating variable. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to MSME owners in Jepara Regency. A total of 140 respondents were selected using purposive sampling, and the data were analyzed using Structural Equation Modeling (SEM) with SmartPLS version 4.0. The results indicate that customer engagement and e-commerce utilization have significant positive effects on product innovation and MSME performance. E-commerce shows a strong direct effect on product innovation (β = 0.589, p < 0.001) and MSME performance (β = 0.409, p < 0.001), while customer engagement significantly influences product innovation (β = 0.484, p < 0.001) and performance (β = 0.566, p < 0.001). Product innovation is also proven to mediate the relationship between customer engagement and MSME performance as well as between e-commerce and MSME performance. The model explains 67.8% of the variance in product innovation (R² = 0.678) and 59.4% of the variance in MSME performance (R² = 0.594), indicating a moderate to strong explanatory power. These findings highlight the importance of strengthening digital customer engagement strategies and optimizing e-commerce utilization to enhance innovation and improve MSME performance sustainably.